A randomized, double-blind, placebo-controlled, short-term monotherapy study of doravirine in treatment-naive HIV-infected individuals. (2nd January 2016) - Schürmann, Dirk; Sobotha, Christian; Gilmartin, Jocelyn; Robberechts, Martine; De Lepeleire, Inge; Yee, Ka Lai; Guo, Ying; Liu, Rachael; Wagner, Frank; Wagner, John A.; Butterton, Joan R.; Anderson, Matt S.
Abstract : Objective: To assess the antiviral activity, pharmacokinetics, and safety of doravirine in nonnucleoside reverse transcriptase inhibitor-naïve, HIV-infected men. Design: Double-blind, randomized, two-panel, dose-escalation study. Methods: In two sequential panels, 18 individuals received doravirine [25 mg (Panel A) or 200 mg (Panel B)] or matching placebo once daily for 7 days. Plasma samples were collected daily for measurement of HIV-1 RNA levels and doravirine pharmacokinetics. Results: For the mean change from baseline in HIV RNA (log10 copies/ml) at 24 h after the day 7 dose, the mean difference (90% confidence interval) between doravirine and placebo was –1.37 (–1.60, –1.14) in the 25-mg group and –1.26 (–1.51, –1.02) in the 200-mg group. None of the participants had viral breakthrough. Increases in mean AUC0–24 h, Cmax, and C24 h were slightly less than dose-proportional, with median Tmax of 1.0–2.0 h. Steady state was achieved after 3–5 days of once-daily dosing. At steady state, accumulation ratios (day 7/day 1) for AUC0–24 h, Cmax, and C24 h were 1.2–1.6. The calculated effective t 1/2 (10–16 h) was similar to that in HIV-uninfected individuals. Adverse events were limited in number, transient, and generally mild to moderate in intensity. One participant had a serious adverse event of elevated liver enzymes (judged probably not drug related) in concurrence with a newly acquired hepatitis C infection. Conclusion: Doravirine monotherapy demonstrated robust antiviral activity at both dose levels, without evidence of viral resistance, and was generally well tolerated. Doravirine pharmacokinetics in HIV-infected individuals were similar to those in uninfected individuals receiving similar doses in prior studies.